2022
DOI: 10.15403/jgld-4196
|View full text |Cite
|
Sign up to set email alerts
|

Romanian Guidelines for the Diagnosis and Treatment of GERD-induced Respiratory Manifestations

Abstract: Background and Aims: Gastroesophageal reflux disease (GERD) is a common condition present in daily practice with a wide range of clinical phenotypes. In this line, respiratory conditions may be associated with GERD. The Romanian Societies of Gastroenterology and Neurogastroenterology, in association with the Romanian Society of Pneumology, aimed to create a guideline regarding the epidemiology, diagnosis and treatment of respiratory conditions associated with GERD.Methods: Delphi methodology was used and eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 223 publications
0
1
0
1
Order By: Relevance
“…In the previous clinical observation study, the use of PPI to treat GERD was not associated with incident asthma [ 7 , 20 , 21 ]. Ruigómez et al used data from the UK General practice research database and showed that patients treated for GERD with PPI had no significant increased risk of developing asthma (RR: 1.2, 95% CI: 0.9–1.6) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous clinical observation study, the use of PPI to treat GERD was not associated with incident asthma [ 7 , 20 , 21 ]. Ruigómez et al used data from the UK General practice research database and showed that patients treated for GERD with PPI had no significant increased risk of developing asthma (RR: 1.2, 95% CI: 0.9–1.6) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Отчасти они рассмотрены в рекомендациях по ведению пациентов с хроническим кашлем [6]. В 2022 г. опубликованы Румынские рекомендации по диагностике и лечению больных с пульмонологическими проявлениями ГЭРБ [7].…”
Section: Introductionunclassified